Amari and the despicable wonders - Alston, B. B. (Alston, B. B. Supernatural investigations ;, 2024)
"War has come to the supernatural world, and Amari's two worst enemies are leading the charge. Elaine Harlowe has manipulated her way into becoming prime minister, using her mind control ability to force the Bureau to take up her vicious grudge against magiciankind. Meanwhile, Dylan Van Helsing, the newly crowned leader of the League of Magicians--and Amari's former partner--is after a destructive new power that would not only ensure the magicians' victory . . . it would make him invincible. With neither the Bureau nor the League safe for Amari, and her newly returned brother, Quinton, determined to keep her out of the fray, she and her friends decide to find a way to end the war on their own. So when they learn that the only way to stop Dylan is to find powerful magical inventions known as Wonders, they go after them. But wielding these items comes at a terrible cost, and Amari will have to decide just how much she's willing to sacrifice . . . because the Despicable Wonders will demand everything"--